1987
DOI: 10.1080/00071668708416992
|View full text |Cite
|
Sign up to set email alerts
|

Dietary iron and broiler performance

Abstract: 1. An experiment was conducted with female broilers from 1 to 39 d of age in which the effects of increasing amounts of extra dietary ferrous sulphate on growth performance, some haematological measurements and Fe, Zn and Cu status were studied. A conventional maize-soyabean diet (107 mg Fe/kg) was supplemented with 0, 20, 60, 180, 540 and 1620 mg Fe to provide 6 treatments. 2. Weight gain responses rose to a plateau between 20 and 60 mg added Fe/kg diet, but further additions of Fe increasingly depressed grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…In this study, the apparent iron requirement was 100 mg/kg diet (80 mg from dietary components and 20 mg from supplemented iron). These results were similar to those found in the present study, indicating that excessive amounts of iron in broiler diets may compromise their performance [ 21 ].…”
Section: Resultssupporting
confidence: 92%
“…In this study, the apparent iron requirement was 100 mg/kg diet (80 mg from dietary components and 20 mg from supplemented iron). These results were similar to those found in the present study, indicating that excessive amounts of iron in broiler diets may compromise their performance [ 21 ].…”
Section: Resultssupporting
confidence: 92%
“…Moreover, in these earlier studies, growth performance, Hb concentration and haematocrit were often used to assess Fe requirements in chicks fed purified or semi-purified diets, and the Fe requirements for broilers during days 1-21 (or days 1-29) were defined as 45-85 mg/kg (4,5,6,(33)(34)(35) . On the other hand, Vahl et al (36) and Ma et al (18) reported that the Fe requirements in broilers fed a practical maize-soyabean-meal diet were 100 and 118 mg/kg for the optimum growth from 1 to 21 or 1 to 39 d of age, respectively. The Fe requirements in broilers fed the practical diets are higher than requirements for those fed purified or semi-purified diets, which might be due to the adverse effect of phytate and fibre on Fe absorption (7)(8)(9) .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the growth performance is always influenced by the type of diets or growth phase and, thus, it might not be a good index for assessing Fe requirements for broilers. Besides, many studies have demonstrated that haematological indices, such as Hb concentration or haematocrit, could reflect the Fe nutritional status or be a sensitive criteria for estimating the Fe requirement of broilers fed purified or semi-purified diets (4,36) . Ma et al (37) found that blood Hb concentration and haematocrit of chicks fed a casein-dextrose diet increased linearly as dietary Fe level increased; Davis et al (4) reported that the Fe requirements of chicks fed a soyabean protein-casein-gelatin diet were 78 and 77 mg/kg for Hb concentration and haematocrit, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…We increased the iron added up to 1,200 and 2,400 mg/kg in the two trial groups during 22–42 days in the subsequent trial and also found no adverse effect on growth performance, even some characteristics of oxidative stress disappeared on the 42 days old (data not shown). However, other study determined the higher Fe concentration (1,620 mg/kg) in diet which produced adverse effects including less body weight and feed conversion rate, and more leg disorders in broilers (Vahl & Van’ T Klooster, ).…”
Section: Discussionmentioning
confidence: 99%